STORAGE OF SALMONELLA, ESHIRICHIA AND STAPHYLOCOCCUS IN SOME DAIRY PRODUCTS DURING ITS STORAGE AT DIFFERENT TEMPERATURES. - Shaikulov Hamza Shodievich; Bobokandova Mehriniso Fazliddinovna (Scholar Express Journals, 2023)
The article discusses the preservation of salmonella, Escherichia coli and staphylococci in cottage cheese when stored at room conditions (at a temperature of 20-24°C) and in a refrigerator (at a temperature of +3°C.). The main attention is paid to the identification of the terms of survival of crops in cottage cheese during interval studies.
Keywords: S. enteritidis gartneri; E. coli; Staphylococcus aureus; Staphylococcus epidermidis